First total synthesis of the only known 2-isopropyliden-2: H -benzofuran-3-one isolated from V. luetzelburgii - Pergomet, Jorgelina Leonor (2017)
The first total synthesis of 5-(1-hydroxy-1-ethyl)-2-isopropyliden-2H-benzofuran-3-one, is reported in its racemic and in one of its optically active [(S)-(-)] forms. This heterocycle, isolated from Verbesina luetzelburgii, is the only known 2-isopropyliden-2H-benzofuran-3-one produced by species of Verbesina. The sequence took place in eight steps and 19% overall yield (up to 33% for the chiral form), from 4′-hydroxyacetophenone. It entailed carbonyl group protection as the 1,3-dioxolane and a phenol ortho formylation, followed by a Williamson etherification with chloroacetone and an organocatalytic cross-aldolization, to afford a 2-acetyl-2,3-dihydrobenzofuran-3-ol intermediate. The latter underwent a methyl Grignard addition to the carbonyl moiety, followed by selective oxidation of the benzylic alcohol and deprotection, resulting in a β-hydroxy diketone derivative. A MsCl-assisted dehydration of the tertiary alcohol, established the isopropylidene motif, whereas the syntheses culminated by chemical or enzymatic (carrot, celeriac) selective reductions of the exocyclic carbonyl group.